RISK FACTORS FOR THE DEVELOPMENT OF CHRONIC KIDNEY DISEASE - Jabbarov O. O.; Erkinova L. O.; Tursunova L. D.; Khuzhaniyazova N. K. (Modern American Journals, 2025)
Chronic kidney disease (CKD) is currently the leading cause of disability and mortality in patients with diabetes mellitus (DM). Developing in 40-45% of patients with both insulin-dependent (IDDM) (type I) and non-insulin-dependent (NIDDM) (type II) diabetes, this formidable complication leads to the development of chronic kidney disease and, ultimately, to death from uremia. Kidney damage in diabetes was first described by R. Kimmelstiel and C. Wilson in 1936. Clinically, it is characterized by the following manifestations: increasing proteinuria (with unchanged urinary sediment), arterial hypertension, the development of nephrotic syndrome (in approximately 30% of patients), and a progressive decrease in renal filtration function. The insidiousness of this complication of diabetes is that it develops gradually and remains unnoticed for a long time, since in the initial stages it does not cause discomfort to the patient. In the late stages, when the presence of chronic kidney disease is already established, preventing its further progression is extremely difficult, and often impossible. The results of our study suggest that metabolic, hemodynamic, and genetic factors play a significant role in the development of chronic kidney disease in patients with type 2 diabetes in the study group.
Keywords: Gene, polymorphism, allele, genotype, albuminuria, glomerular filtration rate, renal hemodynamics, chronic kidney disease.